Food flavors chemical, sensory and technological properties - Jelen, Henryk (CRC Press, 2012)
"Examining the importance of flavor compounds in the production, processing, and storage of foods, this book begins with an introduction to the chemical and sensory aspects of food flavors. Detailing the formation of specific flavors in foods, it emphasizes flavor precursors, presents universal mechanisms and pathways in aroma compound biogenesis, and focuses on the interaction of flavor compounds with proteins, lipids, and saccharides. Describing typical flavors for various food groups, it explains the use of flavor/volatile compounds in the assessment of food safety and concludes with an analysis of key aroma compounds and methods used for screening/comparison"-- Provided by publisher.
Keywords: Flavor.; Food -- Analysis.; Food -- Composition.; Food -- Biotechnology.; elektronické knihy; electronic books